Illocutionary Revelations: Yucatec Maya Bakáan and the Typology of Miratives. (30th January 2018) - AnderBois, Scott
Abstract: Miratives have often been thought of as expressing predications which can be schematised as ' p is Y for the speaker at the time of the utterance', where Y is a member of the set (surprising, new information, a sudden revelation, …). While much of the prior literature has discussed the value of Y, this discussion has typically been taken to be primarily a matter of analysis or its conceptual underpinnings rather than an empirical one. In this paper, I examine a new mirative in detail, Yucatec Maya (YM) bakáan, using context-relative felicity judgments to argue that bakáan conventionally encodes sudden revelation rather than these other notions. While I hold that bakáan encodes revelation, I argue that this revelation is not in fact about propositional content per se, but rather is about the appropriateness/utility of the illocutionary update the speaker performs. A sudden revelation that a proposition is true is one such revelation, but other kinds are more clearly illocutionary in nature. Evidence for this position comes not only from bakáan in declarative sentences, but also its use in imperatives and interrogatives. I argue that the range of uses that the use of bakáan as an illocutionary modifier across sentence types sheds light on the kinds of updates they encode, and in particular supports a theory in which declarative updates are more complex than corresponding imperative and interrogative ones.